Influence of Febrile Neutropenia Period on Plasma Viscosity at Malignancy - Ibrahim Tek; Selami Kocak Toprak; Efe Hasdemir; Samed Rahatli; Aysegül Yesilkaya (The Scientific World Journal)
Cancer, chemotherapy, and infections all together make changes in blood rheology and may affect the defense mechanisms by changing the thrombocyte function and endothelial cell. We have examined changes of blood rheology on plasma viscosity to put on probable following criteria for starting the treatment of febrile neutropenia immediately. A total of 27 postchemotherapy patients (16 males and 11 females) with febrile neutropenia diagnosed according to international guidelines have been included into the study. The plasma viscosity of the patients whose febrile neutropenia has been successfully treated was also measured to assess the impact of the duration of neutropenia on viscosity. The plasma viscosities of the patients were significantly higher during neutropenic episode than in nonneutropenic state () except for alkaline phosphatase. All study parameters, particularly acute phase reactants, were statistically similar during both states. In the correlation of analysis with study parameters and stages, significant correlation was not observed between plasma viscosity alteration and leukocyte-neutrophil alteration, also other study parameters. We have demonstrated significantly elevated plasma viscosity in our patients during febrile neutropenic episode. Despite normal values of various parameters known to trigger plasma viscosity, particularly fibrinogen, it can be easily argued that the main mechanism may be the endothelial injury during infectious process and immune response mediated microcirculatory blood flow alterations.